Natural course of high-grade dysplasia in Barrett’s esophagus: a scoping review and case series - Verheij, Eva P.D.; van Munster, Sanne N.; Chan, Man Wai; Malekzadeh, Arjan; Cotton, Cary C.; Weusten, Bas L.A.M.; Alvarez Herrero, Lorenza; Koch, Arjun D.; Nagengast, Wouter B.; Westerhof, Jessie; Houben, Martin H.M.G.; Shaheen, Nicholas J.; et al. (Gastrointestinal endoscopy, 2025)
Endoscopic eradication therapy (EET) for Barrett’s esophagus (BE) with high-grade dysplasia (HGD) aims to prevent progression to life-limiting cancer. However, HGD patients with a short life expectancy realize limited gains from this approach owing to competing mortality. Clinicians are poorly equipped to counsel such patients, because there is little data regarding survival in untreated HGD. We aimed to evaluate existing literature and describe a case series of patients with untreated HGD. We systematically reviewed Medline, Embase, and Cochrane Library, selecting studies describing the natural history of untreated HGD in BE. The primary outcomes were symptomatic esophageal adenocarcinoma (EAC) and EAC-related death. In addition, cases in which HGD was left untreated were retrospectively identified in the Netherlands. We assessed the time until progression to clinically evident EAC. A total of 3229 studies were identified, of which 3 were included. In 1 study, progression from HGD to clinically evident EAC occurred in 4 subjects after a median of 34 months. The remaining 2 cases progressed to clinically evident EAC after 70 and 115 months. In our previously unreported case series, 11 Dutch patients with flat HGD (n = 3) or HGD in a visible abnormality (n = 8) were included. Four of these 11 patients progressed to clinically evident EAC after a median 52 months (range, 17-78 months). The lag-time between the diagnosis of HGD and progression to clinically evident EAC varied from 1.5 to 10 years. EET for BE with HGD in patients with less than 3 years of life expectancy seems unlikely to be beneficial. These results may guide management decisions for patients with BE. (Netherlands Trial Registry, NL7039; NL-OMON29089.)